THE INFLUENCE OF EASTERN PHILOSOPHY ON WESTERN LITERATURE: A CROSS-CULTURAL EXAMINATION - Axmadjonova Nafosat Xayrullojon qizi The student of Chirchik State Pedagogical University Scientific adviser: Mavluda Abduvaliyevna Komiljonova Teacher, Chirchik State Pedagogical University (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This paper explores the profound impact of Eastern philosophical traditions on Western literature, examining how key tenets of Buddhism, Taoism, Confucianism, and Hinduism have shaped literary movements, thematic developments, and character construction in Western works. Through a comparative analysis, this study highlights specific instances where Eastern thought has inspired Western authors, from the Transcendentalist movement to postmodern narratives. The research contextualizes the integration of Eastern philosophy within Western literary traditions, tracing the intercultural exchanges that facilitated this cross-pollination from the 19th century to the present. This paper concludes that Eastern philosophy continues to serve as a wellspring of inspiration, fostering new modes of expression and enriching the literary landscape.